2013
DOI: 10.1097/ftd.0b013e3182803d16
|View full text |Cite
|
Sign up to set email alerts
|

An Audit of Therapeutic Drug Monitoring Services of Anticonvulsants at a Tertiary Care Hospital in India

Abstract: TDM continues to remain an important tool to support dose individualization when the patient is receiving multiple AEDs or other drugs such as antitubercular medicines, to assess compliance, and to monitor and treat toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…Although this sometimes might be related the patients’ clinical status, however, sub-therapeutic concentrations may lead to the failure of therapy and development of resistance to some drugs like antibiotics and might also lead to increased length of hospitalization and health care costs. This trend has also been observed elsewhere (Ratanajamit et al, 2009, Dalaklioglu, 2013, Taur et al, 2013). Sub-therapeutic concentrations should be as clinically alarming as toxic concentrations as failure of therapy and appearance of toxicity should be considered equally.…”
Section: Discussionsupporting
confidence: 88%
“…Although this sometimes might be related the patients’ clinical status, however, sub-therapeutic concentrations may lead to the failure of therapy and development of resistance to some drugs like antibiotics and might also lead to increased length of hospitalization and health care costs. This trend has also been observed elsewhere (Ratanajamit et al, 2009, Dalaklioglu, 2013, Taur et al, 2013). Sub-therapeutic concentrations should be as clinically alarming as toxic concentrations as failure of therapy and appearance of toxicity should be considered equally.…”
Section: Discussionsupporting
confidence: 88%
“…One study showed that although TDM helped in distinguishing nonresponders due to noncompliance, the "reference range" of the drugs did not reliably predict breakthrough seizures or toxicity (Harivenkatesh et al, 2015). The latter finding had been seen previously in a study in which among patients clinically suspected of having phenytoin toxicity, only 59% had plasma concentrations above the reference levels (Taur et al, 2013). Another study emphasized the need for monitoring the serum levels of even newer antiepileptics like levetiracetam as its levels decreased by about 57% when enzyme inducers were used concomitantly (Gupta et al, 2016).…”
Section: Therapeutic Drug Monitoring (Tdm)mentioning
confidence: 88%
“…Consensus is reached on the rational prescription of TDM, which is – despite recent advancements – a demanding procedure with non-negligible costs for the healthcare systems, both in high- (Schumacher and Barr, 2001; Ghiculescu, 2008; Kang and Lee, 2009; Buclin et al, 2012) and low- (Taur et al, 2013; Nwobodo, 2014) income countries. Guidelines recommend TDM when the following circumstances occur (Gross, 2001; Schumacher and Barr, 2001; Touw et al, 2005; Buclin et al, 2012): (1) when there is a stronger (and ascertainable) relationship between the drug concentration and its therapeutic effect or toxicity, rather than between the administered dose and the effect.…”
Section: Therapeutic Drug Monitoring: a Little Explored Field For Poc?mentioning
confidence: 99%